2014
DOI: 10.5152/eurjrheum.2014.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the metabolic syndrome in rheumatoid arthritis

Abstract: The evaluation of patients with RA for MetS, which is a multidimensional risk factor of CVD, may be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Similar to the present study, Karvounaris et al 10 conducted a study of 200 patients with RA to evaluate MetS and reported the prevalence of MetS among the patients to be 44%. In contrast to that and the current study, Özmen et al 11 and Mok et al 12 reported MetS prevalence of 28.8% and 20% in patients with RA. A difference fact was observed.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to the present study, Karvounaris et al 10 conducted a study of 200 patients with RA to evaluate MetS and reported the prevalence of MetS among the patients to be 44%. In contrast to that and the current study, Özmen et al 11 and Mok et al 12 reported MetS prevalence of 28.8% and 20% in patients with RA. A difference fact was observed.…”
Section: Discussioncontrasting
confidence: 99%
“…In some studies, it has been shown that CVD rate is increased in RA (4,6,27,28). However, the evaluation of risk factors for CVD in this group of patients was restricted.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence regarding the impact of MetS on RA is mixed. Several studies that assessed patients with RA with MetS showed this population is more likely to have higher Health Assessment Questionnaire (HAQ) scores than patients without MetS; however, other studies have not shown a significant difference 37‐41 . Two large‐scale studies that included 100 patients showed that MetS was associated with high systemic inflammatory markers, disease activity, and disability scores compared with patients with RA but without MetS 42,43 .…”
Section: Discussionmentioning
confidence: 99%